الوسائل العملية لتحقيق الفناء في اإلسالم و البوذية = The path to attain al-Fana’ in Islam and Buddhism - Ahmad, Masitoh; Hashim, Jamil (Universiti Sultan Azlan Shah (USAS), 2013)
The objective of this article is to highlight points of convergency and dissimilarities in the teachings of Buddhism and Sufism in the the aspect of spirituality. It describes the path of a wayfarer in his spiritual journey to attain fana’, the highest achievement and the final state of spiritual experiences in the teachings of Islamic Mysticism, and also Buddhist paths to attain Nirvana, the ultimate goal of Buddhist life. The practices and the strict code of ethics in the process of self-purification or purification of the soul, in the spiritual path to attain the the ultimate goal in the teachings of both Sufism and Buddhism are also discussed.